Lotze on Comparison and the Unity of Consciousness. Issue 5 (16th July 2022) - Textor, Mark
Abstract: Hermann Lotze argued that the fact that consciousness simultaneously "holds objects together as well as apart" such that they can be compared implies (a) that there is a simple thinker and (b) that consciousness is an 'indivisible unity.' I offer a reconstruction and evaluation of Lotze's Argument from Comparison. I contend that it does not deliver (a) but makes a good case for (b). I will relate Lotze's argument to the contemporary debate between "top-down" and "bottom-up" views of the unity of consciousness and locate it in its historical context. (Kant and Herbart figure prominently here.)